Feminization of raibow Iriatherina werneri (Meiken, 1974) using estradiol-17β hormone - Rodhi Firmansyah; Odang Carman; Dinar Tri Soelistyowati (Jurnal Iktiologi Indonesia, 2016)
Feminization of the rainbow (Iriatherina werneri) is an initial step to get the functional females (XY). If those functional females crossbreeding with normal males (XY), we will produce super males (YY) individuals. This study aimed to evaluate the optimum condition of feminization on I. werneri using estradiol-17β hormone treatment at different doses and immersion duration with a completely randomized factorial design which consists of different doses and immersion durations with three replicates. The data were analyzed statistically ( ANOVA ). Eyed stage embryos were immersed in 0, 200, 400 and 600 μg L-1 of estradiol-17β for six, 12 and 18 hours; and then the larvae were reared up to 70 days. The results showed that estradiol-17β treatments could increase the percentage of I. werneri female. The doses of 400 and 600 μg L-1 for both six and 12 hours immersion could increase the percentage of female significantly (p<0.050) with value ranged from 85,56-92,22%. The duration of estradiol-17β immersion significantly affected (p<0,05) the I. werneri survival rate. The duration of immersion for six hours showed the highest survival rate. On the other hand, both of doses and duration of immersion did not affect the hatching rate of I. werneri (p>0.05) Abstrak Pembetinaan ikan pelangi (Iriatherina werneri) adalah langkah awal untuk mendapatkan individu betina fungsional (XY). Jika individu betina fungsional ini dikawinkan dengan jantan normal (XY) akan menghasilkan individu ikan jantan super (YY). Penelitian ini bertujuan untuk mengevaluasi kondisi optimum dosis dan lama perendaman yang berbeda untuk pembetinaan ikan pelangi dengan menggunakan hormon estradiol-17β yang dirancang menggunakan rancangan acak lengkap pola faktorial yang terdiri atas faktor dosis dan lama perendaman masing-masing diulang tiga kali kemudian data dianalisis secara statistik (ANOVA). Telur ikan pelangi stadia embrio bintik mata direndam dalam larutan estradiol-17β dosis 0, 200, 400 dan 600 μg L-1 selama 6, 12, dan 18 jam, kemudian larva dipelihara selama 70 hari. Hasil penelitian menunjukkan bahwa perlakuan estradiol-17β dapat meningkatkan persentase betina; dosis 400 dan 600 μg L-1 selama 6 dan 12 jam meningkatkan persentase betina secara nyata (p<0,05) dengan nilai 85,56-92,22%. Lama perendaman berpengaruh nyata (p<0,05) terhadap tingkat kelangsungan hidup dan perendaman selama enam jam memberikan hasil yang terbaik. Sementara itu, dosis dan lama perendaman tidak memengaruhi tingkat penetasan (p>0,05).